Library wars. 6, Love & war - Yumi, Kiiro (Shojo beat manga., 2011)
"It's Valentine's Day, and Iku's hopes are dashed when Dojo, the guy she's been crushing on--and who's her Library Force superior!--receives an elegant box of chocolates from another woman. Romantic intrigue strikes the whole team as Shibazaki meets a would-be suitor and confides in Iku about her tortured love life. And it seems that Hikaru is being followed by someone from his past"--P. [4] of cover.